2015
DOI: 10.1007/s11010-015-2432-0
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle cell differentiation to an osteogenic phenotype involves matrix metalloproteinase-2 modulation by homocysteine

Abstract: Arterial calcification is common in vascular diseases and involves conversion of vascular smooth muscle cells (VSMCs) to an osteoblast phenotype. Clinical studies suggest that the development of atherosclerosis can be promoted by homocysteine (HCY), but the mechanisms remain unclear. Here, we determined whether increases in HCY levels lead to an increase in VSMC calcification and differentiation, and examined the role of an extracellular matrix remodeler, matrix metalloproteinase-2 (MMP-2). Rat VSMCs were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
1
24
0
1
Order By: Relevance
“…Healthy human impacted third molars with immature roots were collected with informed consents from donors (17)(18)(19)(20) years old) at the Oral and Maxillofacial Surgery Department of Jiangsu Provincial Stomatological Hospital. The experimental procedures were approved by the Ethical Committee of Stomatological School of Nanjing Medical University.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…Healthy human impacted third molars with immature roots were collected with informed consents from donors (17)(18)(19)(20) years old) at the Oral and Maxillofacial Surgery Department of Jiangsu Provincial Stomatological Hospital. The experimental procedures were approved by the Ethical Committee of Stomatological School of Nanjing Medical University.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…Obviously, LCN2 meditated the Tcf7l1 function in keratinocyte differentiation. Given that LCN2 can form complex with either matrix metalloproteinase (MMP)-2 or MMP-9, which are also suggested to be functional in regulating cell differentiation, 9, 10 Xu et al 4 had also investigated the role of MMP-2 and MMP-9 in dysregulated differentiation of keratinocytes. The results showed that upregulation of MMP-2 predominated in Tcf7l1-overexpressing HFKs.…”
mentioning
confidence: 99%
“…Low plasma levels of betaine associate with cardiovascular events [84]. While the direct vascular effect of betaine remains to be explored [85,86], an indirect protective role on vascular health could be speculated given To compare RLS with traditional statistical methods, we performed univariate Spearman's rank correlation and multivariate logistic regression. These analyses revealed certain deficiencies and strengths.…”
Section: Discussionmentioning
confidence: 99%